2019
DOI: 10.1111/pbi.13306
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rubisco content in maize mitigates chilling stress and speeds recovery

Abstract: Many C 4 plants, including maize, perform poorly under chilling conditions. This phenomenon has been linked in part to decreased Rubisco abundance at lower temperatures. An exception to this is chilling-tolerant Miscanthus, which is able to maintain Rubisco protein content under such conditions. The goal of this study was to investigate whether increasing Rubisco content in maize could improve performance during or following chilling stress. Here, we demonstrate that transgenic lines overexpressing Rubisco lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…However, since the 1990s, studies have found that reductions in the activity of Rubisco have little impact on carbon assimilation under normal environmental conditions [ 32 , 33 , 34 ]. Rubisco may not be the primary limiting factor that leads to poor performance under chilling conditions but instead helps plants recover faster from these conditions [ 35 ]. Recent studies have shown that there is a non-regulated enzyme, aldolase, that is sensitive to abiotic stresses [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, since the 1990s, studies have found that reductions in the activity of Rubisco have little impact on carbon assimilation under normal environmental conditions [ 32 , 33 , 34 ]. Rubisco may not be the primary limiting factor that leads to poor performance under chilling conditions but instead helps plants recover faster from these conditions [ 35 ]. Recent studies have shown that there is a non-regulated enzyme, aldolase, that is sensitive to abiotic stresses [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this activator, which removes the RuBisCO inhibitor CAP (2-carboxylarabinitol-1,5-bisphosphate), suggests that the Norwegian population could indeed maintain carbon fixation during the dark winter period. If increased RuBisCO expression in Norwegian winter samples is related to cold-acclimation, as shown in maize (Salesse-Smith et al, 2020), then warmer winters could hinder carbon assimilation and, thus, survival in the future Arctic.…”
Section: Photosynthesis and Carbon Fixation In Wintermentioning
confidence: 99%
“…Thus, it is paramount for peanut growers and researchers to uncover suitable sowing windows and cultivation durations in high-latitude areas to deliver successful peanut production ( Dai et al., 2017 ; Li et al., 2018 ; Virk et al., 2020 ; Zhang et al., 2020 ). For the cropping boundary in the high-latitude crop, especially in response to low-temperature stress, the peanut’s light interception and strong sink demand are the major determinants of high yield and quality ( Bagnall et al., 1988 ; Itoh, 2003 ; Salessesmith et al., 2020 ; Ensminger et al., 2006 ). However, the ES (early sowing) window in the most high-latitude area would naturally subject the crop to a greater probability of chilling exposure.…”
Section: Introductionmentioning
confidence: 99%